Reabilitation marketing: marketing concepts evolution in condition of the changes in the socioecological- economic state of society - Yu.A. Olefirenko; О.М. Olefirenko (Marketing i Menedžment Innovacij, 2010)
This article investigated the problem of changing concepts of marketing in the evolution of the global economy and changing technological structures. Suggested and theoretically described a hypothesis for further development of marketing concepts in line with the rehabilitation of marketing "as a logical reaction to the changes in the socio-ecological-economic state of society.